Analisis Derivatif FHD dan SVD Pada Data Gravitasi GGMPlus untuk Identifikasi Struktur Sesar di Kawasan Geotermal Blawan-Ijen - M. ASRAFI (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The Blawan–Ijen area is one of the geothermal areas influenced by complex geological structures. The study area is located in Bondowoso and Banyuwangi Regencies, East Java, Indonesia, at coordinates 114°–114,329° E and 8,169° 7,831° S. This study aims to identify the distribution and analyze the characteristics of fault structures in the Blawan-Ijen area using the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) methods applied to GGMplus gravity data. The data used in this study consisted of GGMplus gravity disturbance data, which were processed through several stages, including data extraction, Complete Bouguer Anomaly (CBA) map generation, regional and residual anomaly separation using the upward continuation method, and horizontal and vertical derivative analyses. Fault interpretation was conducted based on the correspondence between maximum gradient zones on the FHD map and anomaly value changes on the SVD map. Furthermore, slicing analysis was performed to determine fault characteristics and fault types based on the relationship between the absolute maximum and minimum values of SVD. This study identified seven principal fault structures (P1-P7) within the Blawan-Ijen geothermal area using the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) methods applied to GGMplus gravity data. The interpreted faults mainly follow northwest–southeast and north–south orientations, corresponding well with the lineament patterns derived from the lineament analysis. Slicing results further demonstrate that normal faults dominate the study area, although evidence of reverse faults was also recognized on several cross-sectional profiles. Such a structural pattern suggests that extensional tectonic activity associated with volcanic and caldera environments has played a major role in shaping the regional geology. Moreover, the identified fault systems are interpreted to regulate the circulation of hydrothermal fluids by providing potential pathways for recharge, upflow, and outflow within the Blawan-Ijen geothermal system. These results highlight the capability of integrating FHD and SVD analyses with GGMplus gravity data to effectively identify and characterize fault structures related to geothermal processes.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: FHD; SVD; Sesar; Geotermal; Ijen